2008
DOI: 10.1097/wnr.0b013e3282f8b1a0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to low-intensity magnetic field improves acquisition and maintenance of memory

Abstract: Although past research has suggested that acute exposure to extremely low-frequency magnetic field (ELF MF) impairs learning and memory function, data on chronic exposure remain scarce. In this study, we examined the changes in spatial learning and memory by the Morris water maze test after 4 weeks of daily exposure of rats to a 50-Hz magnetic field of 2 mT for either 1 or 4 h. We found that chronic exposure to ELF MF reduced the latency to find the hidden platform and improved long-term memory of former locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 24 publications
5
25
0
2
Order By: Relevance
“…Behavioural studies on rats and mice indicated reductions in locomotor activity and anxiety behaviour [Choleris et al, 2001], and an impaired spatial learning capacity [Lai et al, 1998;Sienkiewicz et al, 1998]. On the other hand, some studies reported the improvement of spatial memory acquisition [Kavaliers et al, 1996;Liu et al, 2008]. Some results could not be replicated when attempted [Stern et al, 1996].…”
Section: Introductionmentioning
confidence: 97%
“…Behavioural studies on rats and mice indicated reductions in locomotor activity and anxiety behaviour [Choleris et al, 2001], and an impaired spatial learning capacity [Lai et al, 1998;Sienkiewicz et al, 1998]. On the other hand, some studies reported the improvement of spatial memory acquisition [Kavaliers et al, 1996;Liu et al, 2008]. Some results could not be replicated when attempted [Stern et al, 1996].…”
Section: Introductionmentioning
confidence: 97%
“…There is evidence that ELF magnetic waves can affect brain waves but no linear correlation is found between the intensities, frequencies of electromagnetic waves yet and its effects on EEG records [18,22,[26][27][28], therefore, designing an efficient and applicable system with a traditional NF form can be effective in undertaking these waves effects. By using regional exposure and stimulation of some regions of human head, the nonlinear effects of stimulation can be removed.…”
Section: Resultsmentioning
confidence: 99%
“…Some few researchers have focused on MF effects on electrical activity of brain, where the cognitive and perceptual effects of MF exposure were explored [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular Ca 2 homeostasis and oxidative reactions are essential for normal functioning of excitable cells (Aon et al 2008), thus the changes observed in our experiments may be a consequence of the increased production of free radicals after the exposure to MF. This is supported by the model of magnetoreception which is based on the existence of Cryptochrome photoreceptors (CRY) (Foley et al 2011), that generate magneticallysensitive radical pairs in chemical reactions (Ritz et al 2000, Todorović et al 2007) and others in the literature (Pozzi et al 2007, Liu et al 2008, Sun et al 2010, Ilijin et al 2011a, 2011b, Wang et al 2013, Ma et al 2014. M. funereus individuals do not expect intensified MF activity, so the change in the neuronal background activity was irreversible after the initial effect of sine wave MF-5.…”
Section: Discussionmentioning
confidence: 95%